Organ Preservation in Rectal Cancer: The Patients' Perspective - Cihan Gani; Cihan Gani; Cihan Gani; Nina Gani; Sebastian Zschaeck; Fabian Eberle; Norbert Schaeffeler; Thomas Hehr; Bernhard Berger; Stefan Georg Fischer; Johannes Claßen; Stephan Zipfel; et al. (Frontiers in Oncology, 2019)
Organ preservation after a clinical complete response to radiochemotherapy is currently one of the most discussed topics in the management of rectal cancer. However, the patients' perspective has only been poorly studied so far. In this multicenter study, we examined 49 patients with locally advanced rectal cancer. The willingness to participate in an organ preservation study and the acceptance of the associated aspects such as intensified radiochemotherapy protocols, the need for close follow-up examinations and local regrowth rates were assessed. Attitudes were correlated with baseline quality of life parameters and psychological scales for “fear of progression”, “locus of control”, “depression”, and the “willingness to take risks”. A total of 83% of patients would consider the deferral of surgery in case of a clinical complete response (cCR). Three monthly follow-up studies and a 25% local regrowth rate are considered acceptable by 95% and 94% respectively. While 41% would be willing to exchange cure rates for a non-operative treatment strategy, a potentially more toxic radiochemotherapy in order to increase the probability of a cCR was the aspect with the lowest acceptance (55%). Psychological factors, in particular “locus of control” and “willingness to take risks”, influenced patient preferences regarding most of the assessed parameters. While in general a broad acceptance of an organ-preserving treatment can be expected, patient preferences and concerns regarding different aspects of this strategy vary widely and require specific consideration during shared decision making.